Design of knee joint mechanisms and in-socket sensors for transfemoral amputees / Amr Mohammed El-Sayed Ahmed - Amr Mohammed, El-Sayed Ahmed (2015)
Lower limb prostheses are developed to assist amputees in restoring mobility functions such as walking, sit-to-stand, stair ascent/descent, and ramp climbing. Although the current prostheses are equipped with sensors, actuators, controllers, and mechanical structures, they require improvements to mimic the function of the natural limbs. The first challenge in prosthetic development is to monitor the amputee/prosthesis interaction by using sensors built into the socket. This interaction helps in detecting the gait phases and events, in addition to develop new control strategies for prostheses, which may enhance the amputees’ comfort. The second challenge is to develop a knee prosthetic mechanism that could imitate the functions of the natural knee. To accomplish the aims of this thesis, studies were undertaken consecutively. First, the technology of the knee prosthesis was studied to understand the functionality of its components. The technology review showed that the sensory system requires enhancement, in particular, a new sensory system can be added-on to the mechanical sensors to sense the user’s intent, identify the transition between phases, and improve the control performance of the prosthesis. Based on this study, the piezoelectric bimorph (PB) was selected as the sensing element while a linear motor was selected as the most appropriate actuator. Next, the PB was validated as a sensing element by finding out its characteristics for the intended application. The static and dynamic characteristics of the PB were investigated and tested as an in-socket sensor with a transfemoral amputee to check its ability to sense the movement of the knee prosthesis. Moreover, the PB was tested as an actuation element in an application named microgripper that was capable of grasping a small object. Also, the PB was compared with a force sensitive resistor (FSR) as an in-socket sensor for a transfemoral amputee performing activities such as walking, sit-to-stand, and stair climbing. The PB could track the knee angle at most of the activities, while the FSR could be used as a trigger sensor at different movements. In the second stage, the focus was on the actuation system and mechanical structure of the knee prosthesis. It was found that, the mechanical actuation system needs improvement in terms of the normal range of motion and the power generation in activities that require extra torque and power. Therefore, a new design of knee prosthesis mechanism that contains a linear actuation system was presented and modeled using a physical modelling tool. The mechanism was physically simulated and controlled using PID controller at activities of daily living (ADL). Finally, an overall control framework of the knee mechanism using in-socket sensor was presented to guide the researchers to develop a knee prosthesis that could be controlled using in-socket sensors. In conclusion, the study demonstrates the possibility of using the piezoelectric bimorph as an in-socket transducer. Furthermore, a knee prosthesis mechanism was successfully designed, modelled, and tested at ADL. Further, clinical trials are recommended for the knee mechanism upon future development. Moreover, more subjects with different types of sockets may be tested towards improving the functionality of the knee prosthesis